Student’s Perception on the Implementation of “English with Emma” YouTube videos as a Vocabulary Building Strategy at SMKN 1 Padang - Afif, Ahmad Fajar; Rani, Yati Aisya (Universitas Negeri Padang, 2024)
This study aim to figure out How is the Students' Perception on the Implementation of